Fluorescein Application in Cranial and Spinal Tumors Enhancing at Preoperative MRI and Operated With a Dedicated Filter on the Surgical Microscope: Preliminary Results in 279 Patients Enrolled in the FLUOCERTUM Prospective Study - Falco, Jacopo; Cavallo, Claudio; Vetrano, Ignazio G.; de Laurentis, Camilla; Siozos, Lampros; Schiariti, Marco; Broggi, Morgan; Ferroli, Paolo; Acerbi, Francesco (Frontiers in Surgery, 2019)
Objective: Sodium fluorescein, a green, water soluble dye, is used as neurosurgical fluorescent tracer thanks to its property to accumulate in cerebral regions of blood-brain barrier (BBB) disruption. The authors report the preliminary results of a prospective observational study regarding the use of fluorescein-guided technique for the resection of suspected malignant neoplasms of the central nervous system (CNS), contrast enhancing at preoperative magnetic resonance imaging (MRI), using a dedicated filter on the surgical microscope. Methods: In March 2016 the authors started a prospective, observational trial to evaluate intraoperative fluorescence's characteristics of CNS tumors, the percentage of extent of resection thanks to fluorescein aid and side effects related to fluorescein administration. This report is based on a preliminary analysis of the results of first 279 enrolled patients. Fluorescein was intravenously injected after intubation or immediately at the entrance in the operating room for awake procedures; the tumor was removed using a dedicated filter on the surgical microscope in an inside-out fashion until all fluorescent tissue was removed, as considered feasible by the surgeon. Results: The 279 patients finally enrolled in the trial, both firstly diagnosed and recurrent, were categorized according to WHO pathological classification and there were 212 neuroepithelial tumors, 25 brain metastases, 10 cerebral lymphomas, 7 hemangioblastomas, or hemangioendotheliomas and 25 other tumors and conditions. No adverse reaction related to the administration of fluorescein or to the combined use of fluorescein with other fluorophores was registered. Fluorescein accumulated in cerebral regions where the BBB was damaged, representing a significant surgical aid in most of the CNS tumors with contrast enhancement. In cases of complete removal of all fluorescent tissue, as intraoperatively judged by the surgeon, postoperative MRI revealed a gross total resection in 181/198 patients (91.4%). Conclusions: Based on these preliminary results, fluorescein-guided surgery with a dedicated filter on the microscope is a safe and effective technique to improve visualization and resection of different CNS tumors and conditions, based on BBB alteration.